Exploring the image language of Mongolian painting from the perspective of regional culture (Mongolian Journal of Arts and Culture, 2024)
Mongolian painting art is influenced by the regional characteristics of Mongolia, and is distinct from other regions and has its unique features. The language of painting images is an artistic expression that combines the creator’s subjective consciousness with objective aims; it is a way for the creator to express emotions and also a bridge for communication between the creator and the viewer. Through the study of the diversity of modern paintings, this article explores the cultural integration behind art and analyses the artistic expression of ethnic elements in paintings. From the perspective of regional culture, this article discusses the influence of Mongolian regional characteristics on Mongolian image language. Painters depict the beauty and vastness of the grassland with their brushes and integrate the long history and traditional folk culture in their creations. Mongolian-themed paintings have unique regional characteristics and ethnic aesthetic features. Taking the regional characteristics of Mongolian paintings as the entry point, it demonstrates the significance and uniqueness of Mongolian painting image language for artistic creation.Монгол зургийн дүрслэлийн хэлийг бүс нутгийн соёлын үүднээс судлах ньХураангуй: Монголын уран зураг нь Монгол орны бүс нутагт тохирсон, бусад бүс нутгаас ялгарах өөрийн гэсэн онцлогтой. Дүрслэх урлаг нь уран бүтээлчийн субъектив ухамсрыг объектив зорилготой хослуулсан уран сайхны илэрхийлэл юм. Өөрөөр хэлбэл, уран бүтээлчийн сэтгэл хөдлөлөө илэрхийлэх гол арга зам бөгөөд уран бүтээлч болон үзэгчийг холбож өгөх гүүр юм. Энэ өгүүлэлд орчин үеийн уран зургийн олон талт байдлыг судалж, угсаатны элементүүд, уран сайхны илэрхийлэлд дүн шинжилгээ хийж, түүгээр дамжуулан соёлын нэгдлийг илрүүлсэн. Монголын бүс нутгийн соёлын онцлог монголын дүрслэх урлагт хэрхэн нөлөөлсөн талаар судалсан. Сүүлийн үед уран зураачид өргөн уудам нутаг, тал хээр, үзэсгэлэнт байгалийг бийрээр дүрсэлж, олон зуун жилийн түүх, ардын уламжлалт соёлыг уран бүтээлдээ шингээн бүтээх нь ихэссэн. Монголын уран зургийн дүрслэлийн хэл нь гоо зүйн онцлог шинжүүдийг агуулж байдаг тул онцгой ач холбогдолтой гэж үзэн энэхүү өгүүллээ бичиглэв.Түлхүүр үгс: угсаатны элементүүд, бэлгэдэл зүй, өнгө ба чимэглэл, зохиомж ба хэлбэр, хүмүүс ба хөрөг зураг, байгаль ба хүрээлэн буй орчин, зөрчилдөөн ба нэгдэл, уламжлал ба орчин үе, илэрхийлэл, гоо зүй